An evaluation model of cortical functions - Ana Guardiola; Liana Lisboa Fernandez; Newra Tellechea Rotta (Arquivos de Neuro-Psiquiatria)
The authors suggest a protocol elaborated to standardize the evaluation of high brain functions that should become an element for localization of cortical pathology.